Degenerations of 3-dimensional nilpotent associative algebras over an algebraically closed field - Ivanova, N. M.; Pallikaros, C. A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.5+514 We determine the complete degeneration picture inside the variety of nilpotent associative algebras of dimension three over an algebraically closed field. As compared with the discussion in [N. M. Ivanova, C. A. Pallikaros, Adv. Group Theory and Appl., 18, 41-79 (2024)], for some arguments in the present article, it is necessary to develop alternative techniques, which are now valid over an arbitrary algebraically closed field. There is a dichotomy of cases concerning the obtained results corresponding to the cases where the characteristic of the field is 2 or not.